Exploring ecosocial contexts of alcohol use and misuse during the COVID-19 pandemic among urban refugee youth in Kampala, Uganda: Multi-method findings - Logie, Carmen H.; Okumu, Moses; Admassu, Zerihun; MacKenzie, Frannie; Tailor, Lauren; Kortenaar, Jean-Luc; Perez-Brumer, Amaya; Ahmed, Rushdia; Batte, Shamilah; Hakiza, Robert; Kibuuka Musoke, Daniel; Katisi, Brenda; et al. (Journal of Migration and Health, 2024)
Urban refugees may be disproportionately affected by socio-environmental stressors that shape alcohol use, and this may have been exacerbated by additional stressors in the COVID-19 pandemic. This multi-method study aimed to understand experiences of, and contextual factors associated with, alcohol use during the pandemic among urban refugee youth in Kampala, Uganda. We conducted a cross-sectional survey (n = 335), in-depth individual interviews (IDI) (n = 24), and focus groups (n = 4) with urban refugee youth in Kampala. We also conducted key informant interviews (n = 15) with a range of stakeholders in Kampala. We conducted multivariable logistic regression analyses with survey data to examine socio-demographic and ecosocial (structural, community, interpersonal) factors associated with ever using alcohol and alcohol misuse. We applied thematic analyses across qualitative data to explore lived experiences, and perceived impacts, of alcohol use. Among survey participants (n = 335, mean age= 20.8, standard deviation: 3.01), half of men and one-fifth of women reported ever using alcohol. Among those reporting any alcohol use, half (n = 66, 51.2 %) can be classified as alcohol misuse. In multivariable analyses, older age, gender (men vs. women), higher education, and perceived increased pandemic community violence against women and children were associated with significantly higher likelihood of ever using alcohol. In multivariable analyses, very low food security, relationship status, transactional sex, and lower social support were associated with increased likelihood of alcohol misuse. Qualitative findings revealed: (1) alcohol use as a coping mechanism for stressors (e.g., financial insecurity, refugee-related stigma); and (2) perceived impacts of alcohol use on refugee youth health (e.g., physical, mental). Together findings provide insight into multi-level contexts that shape vulnerability to alcohol mis/use among urban refugee youth in Kampala and signal the need for gender-tailored strategies to reduce socio-environmental stressors.